2020
DOI: 10.1088/2053-1583/abc73a
|View full text |Cite
|
Sign up to set email alerts
|

Emerging members of two-dimensional materials: bismuth-based ternary compounds

Abstract: Bismuth-based binary compounds, including Bi2Se3 and Bi2Te3, have attracted increasing attention as well-known topological insulators. On the other hand, bismuth-based ternary compounds exhibit diverse properties, such as, ultrahigh carrier mobility, and strong Rashba spin splitting. Moreover, they boast of superior photocatalytic properties, implying great potential to be used in a wide range of applications. The unique structure and properties of two-dimensional (2D) materials, especially the extraordinary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 273 publications
(358 reference statements)
0
18
0
Order By: Relevance
“…[10] The unique structure endows it with outstanding characteristics that cannot be provided by other 2D materials, in addition to further optoelectronic advantages; thus, resulting in a wide range of applications. [11,12] Thus, it is necessary to identify potential 2D bismuth oxychalcogenide nanomaterials and to investigate their characteristics as well as potential applications. Bismuth oxyselenide (Bi 2 O 2 Se) is the first synthesized Bi 2 O 2 X material by gas-phase transport reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] The unique structure endows it with outstanding characteristics that cannot be provided by other 2D materials, in addition to further optoelectronic advantages; thus, resulting in a wide range of applications. [11,12] Thus, it is necessary to identify potential 2D bismuth oxychalcogenide nanomaterials and to investigate their characteristics as well as potential applications. Bismuth oxyselenide (Bi 2 O 2 Se) is the first synthesized Bi 2 O 2 X material by gas-phase transport reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Thereafter, extensive investigations are carried out with focus on the physical and chemical properties, which reveals its outstanding thermoelectric properties, sensible photon response, adjustable bandgap, ultra-fast carrier mobility, and long carrier relaxation time. [11,[15][16][17] The combination of these properties renders it a promising candidate for various novel optoelectronic devices at the near-infrared (NIR) and mid-infrared (mid-IR) regions. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Recently, bismuth oxytelluride (Bi 2 O 2 Te), as a new addition to the bismuth oxychalcogenide family, has attracted increasing research attention.…”
Section: Introductionmentioning
confidence: 99%
“…Bi 2 O 2 Ch (Ch = S, Se, Te) is another class of promising n-type Bi-based oxychalcogenides, which crystallizes in a tetragonal structure (space group: I 4 /mmm ) consisting of alternate layers of insulating [Bi 2 O 2 ] 2+ and conducting Ch 2– square nets stacked along the c -axis, as shown in Figure .…”
Section: N-type Oxychalcogenidesmentioning
confidence: 99%
“…14 2D materials include 2D allotropes of various elements (e.g., graphene, borophene, silicene, phosphorene and germanene) or compounds (e.g., h-BN, g-C 3 N 4 (CN), transition metal dichalcogenides (TMDs), MXenes, layered double hydroxides (LDHs)), whose family is still growing. [15][16][17][18] These 2D materials with unique structural and electronic properties result in extensive breakthroughs in the catalysis and energy conversion fields. [19][20][21] It has been found that 2D semiconductors which have large specific surface areas with abundant surface-active sites could be promising photocatalysts providing superior electron mobility and short diffusion distance for efficient charge separation.…”
Section: Introductionmentioning
confidence: 99%